PENGARUH FRAKSI VOLUME DAN ARAH SERAT TERHADAP KETANGGUHAN IMPAK DAN KEKUATAN BENDING PADA MATERIAL KOMPOSIT SERAT TANDAN KOSONG KELAPA SAWIT - Jefri Aldo; Sunardi; Mekro Permana Pinem; Jefri Aldo (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Natural fiber-based composite materials are becoming an environmentally friendly alternative that continues to be developed due to their abundant availability, light weight, and low production costs. This study aims to determine the effect of volume fraction and fiber direction on the mechanical properties of empty oil palm fruit bunch (OPEFB) fiber-based composites, particularly impact toughness and flexural strength. The composite manufacturing process was carried out experimentally using hand lay-up and compression molding methods. OPEFB fibers were used as reinforcement and polyester resin as matrix, with the addition of MEKPO catalyst at 1% of the resin volume. Composites were varied based on fiber volume fraction (20%, 30%, and 40%) and fiber direction (0°, 45°, and 90°). Impact toughness testing was carried out using the Izod method referring to ASTM D256, while flexural strength was tested using the three-point bending method (ASTM D790). The results showed that a 30% volume fraction with a 0° fiber direction produced the highest flexural strength of 95.7 MPa, while a 40% volume fraction with a 45° direction showed the highest impact toughness of 28.1 kJ/m². Increasing the fiber volume fraction above 30% decreased the flexural strength due to fiber agglomeration. The 0° fiber direction was optimal for flexure, while 45° was most effective for absorbing impact energy.